Influencia del tamaño de muestra en la relación diámetro-altura total en plantas de dos especies forestales en bosque natural, Puerto Almendra, Loreto, Perú- 2021 - Lopez Chuquipiondo, Jack Robinson (2023)
The thesis was carried out at the Arboretum "El Huayo" - FCF - UNAP, San Juan Bautista, Maynas, Loreto. The objective was to determine if the degree of relationship diameter-total height is different in the growth of plants of Perebea guianensis Aubl."chimicua" and Tachigali poeppigiana Tul."tangarana blanca" according to sample size in natural forest. The data were diameter (DAP) and total height of the trees with DAP ? 10 cm of the 2 species studied. The results show that the degree of relationship between these variables for both species was regular in all the samples evaluated; the best fit allometric models for the species Perebea guianensis Aubl.”chimicua” were quadratic, composite and cubic; for the species Tachigali poeppigiana Tul."white tangarana" were: cubic and S-curve.